Interações medicamentosas de fitoterápicos e fármacos: Hypericum perforatum e Piper methysticum - Cordeiro, C. H.G. [UNESP]; Chung, M.C. [UNESP]; Sacramento, L.V.S. do [UNESP] (Sociedade Brasileira de Farmacognosia, 2005)
A utilização de produtos naturais na medicina popular é milenar e persiste até os dias atuais. Entretanto, a idéia de que estes produtos são isentos de toxicidade torna o uso de medicamentos fitoterápicos cada vez maior e indiscriminado. Este trabalho trata de uma revisão sobre as interações que podem ocorrer com a utilização concomitante de Hypericum perforatum L. (erva de são joão) e Piper methysticum F. (kava-kava) com fármacos, podendo levar a sérios efeitos tóxicos, incluindo a fatalidade.

Natural products in popular medicine have been used for hundreds of years and persists nowadays. However, the idea that these products are exempted of toxicity turns the use of herbs to be larger and indiscriminate. This work is a review of interactions that can happen with concomitant use of Hypericum perforatum L. (St. John's wort) and Piper methysticum F. (kava-kava) with medicines that can result in serious toxicological effects including fate.
Drug interactions between herbs and medicines: Hypericum perforatum and Piper methysticum
Keywords: Piper methysticum; Hypericum perforatum; erva de são João; kava-kava; interações medicamentosas; fitoterápicos; Hypericum perforatum; Piper methysticum; St. John's wort; kava-kava; drug interactions; medicines